LANDASAN PENDIDIKAN AGAMA ISLAM DENGAN PROFIL PELAJAR PANCASILA DI ERA KURIKULUM MERDEKA - Afnanda, Mihrab (TARBIYAH DARUSSALAM: JURNAL ILMIAH KEPENDIDIKAN DAN KEAGAMAAN, 2023)
Abstract The first precepts to the fifth precepts contain the foundation of Islamic religious education in the independent curriculum which also places the status of "One God"; "Just and civilized humanity"; "The unity of Indonesia"; "A democracy led by wisdom in representative deliberations"; and "Social Justice for All Indonesian People" is an important basis in the Pancasila profile because the characteristics of students in the independent curriculum are children who are faithful, pious and have good morals towards Allah SWT, fellow human beings, nature, a nation, have a spirit of mutual cooperation, independent, creative, critical reasoning, a sense of global diversity and work hand in hand in collaborating to maintain Indonesian unity, the ability to negotiate well without forcing personal interests, spirited leader and creative in carrying out his rights and obligations towards parents, educators, teaching staff, school principals as well as school institutions and the outside community. This means that there is a close relationship between the foundation of Islamic Religious Education and the Pancasila Student Profile.